13C as an indicator of sources of the settling and sedimentary organic matter in the Gulf of Lions (W Mediterranean) - Faganeli, Jadran (RMZ-materials and geoenvironment, 2003)
The carbon isotopic composition of settling organic matter from sediment traps was determined on a seasonal basis in the Gulf of Lions (W Mediterranean). Isotopic variations reflected the dynamic nature of carbon input to continental shelf environments, which are influenced by phytoplankton blooms in spring and summer, and allochthonous (terrigenous) inputs in winter. The 13Corg isotopic composition of organic matter in surficial sediments suggests that the settling organic matter source was largely phytoplanktonic (marine).
Keywords: isotope; izotopi; Lyonski zaliv; morski sedimenti; ogljik